Prokaryotic Caspase Homologs: Phylogenetic Patterns and Functional Characteristics Reveal Considerable Diversity - Asplund-Samuelsson, Johannes (Public Library of Science, 2012)
Caspases accomplish initiation and execution of apoptosis, a programmed cell death process specific to metazoans. The existence of prokaryotic caspase homologs, termed metacaspases, has been known for slightly more than a decade. Despite their potential connection to the evolution of programmed cell death in eukaryotes, the phylogenetic distribution and functions of these prokaryotic metacaspase sequences are largely uncharted, while a few experiments imply involvement in programmed cell death. Aiming at providing a more detailed picture of prokaryotic caspase homologs, we applied a computational approach based on Hidden Markov Model search profiles to identify and functionally characterize putative metacaspases in bacterial and archaeal genomes. Out of the total of 1463 analyzed genomes, merely 267 (18%) were identified to contain putative metacaspases, but their taxonomic distribution included most prokaryotic phyla and a few archaea (Euryarchaeota). Metacaspases were particularly abundant in Alphaproteobacteria, Deltaproteobacteria and Cyanobacteria, which harbor many morphologically and developmentally complex organisms, and a distinct correlation was found between abundance and phenotypic complexity in Cyanobacteria. Notably, Bacillus subtilis and Escherichia coli, known to undergo genetically regulated autolysis, lacked metacaspases. Pfam domain architecture analysis combined with operon identification revealed rich and varied configurations among the metacaspase sequences. These imply roles in programmed cell death, but also e.g. in signaling, various enzymatic activities and protein modification. Together our data show a wide and scattered distribution of caspase homologs in prokaryotes with structurally and functionally diverse sub-groups, and with a potentially intriguing evolutionary role. These features will help delineate future characterizations of death pathways in prokaryotes.